Hedge fund activism and short-term value creation prior to the initial filing: evidence from US firms. (2nd March 2023) - Karpouzis, Efstathios; Margaritis, Dimitris; Psillaki, Maria; Staikouras, Christos
Hedge funds trade on non-public information which is not clearly disclosed to the market at the time of schedule 13D or 13G filings. Using a hand-collected dataset of US hedge funds interventions we provide new evidence on the value of non-public information at the time the filer surpasses the 5% threshold and the filing obligation is triggered. We find returns are abnormally high prior to the disclosure and more importantly prior to the 5% threshold date but only for schedule 13D events. Both 13D and 13G targeted firms generate abnormal returns in the post filing period which are significantly lower than the 13D returns prior to the filing date. The novelty of our approach is that it distinguishes gains resulting from insider trading around the 5% threshold event from those generated by information asymmetry around the filing event.